Negative spaces of Mumuye figure sculpture—style and ethnicity - Richard Fardon (Afriques)
Revisiting the attribution of figures to Mumuye, provides us with an opportunity to think about the effects of ethnic labelling on our appreciation of ‘precontemporary African art’. By virtue of not being typical, extreme cases throw more general issues into sharp relief. The mismatch between the renown and the documentation of precontemporary Mumuye art has few parallels. Mumuye figures are celebrated as icons of African sculpture by the institutions and personnel of what we have grown accustomed to call the ‘artworld’, one that encompasses museums, galleries and auction houses; publications on Mumuye ethnography, language and history in what, for convenience, we can contrast as the ‘ethnoworld’ continue to draw upon research undertaken a half century ago or earlier. Artworld and ethnoworld discourses have diverged, even about fundamental questions of identity. What is the relationship, for instance, between the ethnoworld’s understanding of Mumuye ethnicity and the artworld’s use of the ethnic adjectice in ‘Mumuye style’? A handful of Mumuye objects were collected before the Nigerian Civil war (1967–1970) during which most of those the artworld would consider ‘authentic’ left the country. This emptying of the local reservoirs has created a negative space that invites efforts at repair, not least because, like other markets, the art market abhors a vacuum. Understanding the histories of precontemporary Mumuye artworks requires careful methodology and a realistic acceptance of the likely limits of knowledge. Scholarly attention continues to find value in existing documentation, though with necessarily diminishing returns. Interesting insights have also been derived from parts of the overall assemblage of artworks attributed to the Mumuye. If the artworld took lead responsibility for a catalogue raisonné that reassembled the decade-long outflow from the late 1960s this would enable a more systematic approach to what are currently piecemeal attempts to map formal resemblances in artworks.